Health-related outcomes, health care resource utilization, and costs of multiple sclerosis in Japan compared with US and five EU countries - Yamabe K; DiBonaventura MD; Pashos CL (Dove Medical Press, 2019)
Kaoru Yamabe,1 Marco D DiBonaventura,2 Chris L Pashos3 1Healthcare Policy and Access, Takeda Pharmaceutical Company Limited, Chuouku, Tokyo 103-8668, Japan; 2Health Outcomes, Kantar Health, New York, NY 10010, USA; 3Global Outcomes and Epidemiology Research. Data Sciences Institute, Takeda Pharmaceutical International, Cambridge, MA 02139, USA Purpose: Multiple sclerosis (MS) imposes a huge burden on patients. This study examined the relationship between MS and health-related and economic burden in Japan; secondarily, health status was compared across patients with MS in Japan, US, and five European Union (5EU) countries (France, Germany, Italy, Spain, and UK).Methods: A retrospective cross-sectional study was conducted using self-reported data from 2009 to 2014 Japan National Health and Wellness Survey (n=145,759). Health status, work productivity loss, activity impairment, health care resource utilization, and annual costs associated with MS (n=85) were compared with controls without MS (n=145,674). Propensity score matching and multivariable linear regressions determined the effect of MS after controlling for confounders. Health status in Japan was also compared with that of 5EU (n=62) and US (n=67) patients with MS.Results: Patients with MS in Japan reported significantly worse health status via mental component summary score (MCS; 40.1 vs 45.8) and physical component summary score (PCS; 41.4 vs 51.2) and health state utility scores (0.63 vs 0.74; all P<0.001). They also reported more absenteeism (12.0% vs 3.7%), presenteeism (33.8% vs 19.8%), overall work impairment (40.9% vs 21.6%), and activity impairment (43.6% vs 24.0%), with higher indirect costs (¥2,040,672/US $20,102 vs ¥1,076,306/US$10,603) than controls (all P<0.001). Patients with MS reported higher resource use, including provider visits (8.0 vs 4.7), emergency room visits (0.03 vs 0.1), and hospitalizations (2.7 vs 0.69) in the past 6 months, with higher direct costs (¥3,670,906/US$36,162 vs ¥986,099/US$9,714) than controls (all P<0.001). Finally, Japanese patients with MS reported lower MCSs and higher PCSs than their US and 5EU counterparts.Conclusion: MS in Japan is associated with poor health status and high work productivity loss, resource use, and costs, underscoring the need for improved treatment, especially vis-à-vis mental health, when comparing Japanese patients with their 5EU and US counterparts. Keywords: activity impairment, direct costs, health care resource utilization, health status, indirect costs, work productivity impairment